Risk assessment of type-2 diabetes using the Indian diabetes risk score: a cross-sectional study on medical students from a tertiary care hospital - Pandey, Aditya; Patel, Amit (International Journal Of Community Medicine And Public Health, 2021)
Background: Diabetes mellitus is a major public health problem which affects all age groups and has now been identified in young. Indian diabetes risk score (IDRS), devised and developed by Mohan et al. at the Madras Diabetes Research Foundation, is a validated tool to identify individuals with high risk of developing type 2 diabetes mellitus. Methods: Present cross-sectional study was conducted among medical students of a medical college in Jhansi from June 2021 to September 2021. A semi-structured interview schedule for socio demographic details of subjects like age, gender, education/occupation of parents and physical activity. Written informed consent was taken. Statistical analysis used was SPSS trial version was used for data analysis. P<0.05 was considered as statistically significant. Results: A total of 300 medical students were included in the study. IDRS categorization revealed 10 (3.3%) respondents had score >60 (high risk) and 84 (28%) respondents had score between 30-50 (moderate risk). While 206 (68.6%) respondent had score <30 (low risk). Conclusions: Our study supports the use of IDRS method as screening of diabetes at mass level as it is cost effective as well as time saving procedure.